2000
DOI: 10.1177/0022427800037003003
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing the Streets: Harassment and Perceptions of Safety among Women

Abstract: Although research consistently shows that women feel unsafe in a variety of situations, the social sources of these perceptions have not been clearly identified. This article examines, theoretically and empirically, the influence of sexual harassment on perceptions of safety among women. Because perceptions of safety among women are largely related to fears of sexual victimization, sexual harassment, particularly when it involves strangers, should indicate sexual vulnerability and typify particular contexts as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
153
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(174 citation statements)
references
References 25 publications
15
153
0
5
Order By: Relevance
“…The present findings contribute to the extant objectification literature in several theoretically novel ways. First, although previous researchers have found stranger harassment to be an extremely common form of sexual objectification that women experience in their everyday lives (Fairchild, 2010;Fairchild & Rudman, 2008;MacMillan et al, 2000), with stranger harassment representing one of the most prototypical objectification experiences posited by objectification theorists (Bartky, 1990), only a handful of studies have examined stranger harassment explicitly and its consequences through the objectification framework (Fairchild, 2010;Fairchild & Rudman, 2008). Consistent with both previous research and objectification theory, the current study's findings revealed that more stranger harassment predicted more self-objectification as evidenced by more body surveillance (Fairchild & Rudman, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The present findings contribute to the extant objectification literature in several theoretically novel ways. First, although previous researchers have found stranger harassment to be an extremely common form of sexual objectification that women experience in their everyday lives (Fairchild, 2010;Fairchild & Rudman, 2008;MacMillan et al, 2000), with stranger harassment representing one of the most prototypical objectification experiences posited by objectification theorists (Bartky, 1990), only a handful of studies have examined stranger harassment explicitly and its consequences through the objectification framework (Fairchild, 2010;Fairchild & Rudman, 2008). Consistent with both previous research and objectification theory, the current study's findings revealed that more stranger harassment predicted more self-objectification as evidenced by more body surveillance (Fairchild & Rudman, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Stranger harassment in public spaces also reduces women's perceptions of safety while travelling alone at night (Macmillian et al, 2000) and such experiences indirectly contribute to restricted movements (Fairchild and Rudman, 2008). Adolescent and young adult experiences of 'Eva teasing' (a form of street harassment) are associated with negative emotions and restricted movements (Talboys et al, 2017), avoidance of school (Bhagavatheeswaran et al, 2016), and poorer mental health outcomes and suicidal ideation (Talboys, 2015).…”
mentioning
confidence: 99%
“…Female children, adolescent girls, and adult women report exposure to sexually degrading jokes, being sexually harassed, being called sexual names, having body parts ogled, and being the target of unwanted sexual advances to a significantly greater degree than boys and men (Gardner, 1980;Hill & Fischer, 2008;Klonoff & Landrine, 1995;Kozee, Tylka, Augustus-Running head: OBJECTS AND ACTIONS Horvath, & Denchik, 2007;Macmillan, Nierobisz, & Welsh, 2000;Moradi, Dirks, & Matteson, 2005;Murnen & Smolak, 2000;Puwar, 2004;Swim, Hyers, Cohen, & Ferguson, 2001). Media encounters include the depiction of women as primarily bodies and body parts in magazines, advertisements, TV programming, film, music lyrics and videos, and internet and social networking sites (for reviews, APA, 2007;Calogero, Tantleff-Dunn, & Thompson, 2011;Reichert & Carpenter, 2004).…”
mentioning
confidence: 99%